Fabrication of methylammonium bismuth iodide through interdiffusion of solution-processed BiI3/CH3NH3I stacking layers. Issue 69 (11th September 2017) - Wang, Huijia; Tian, Jianhua; Jiang, Kejian; Zhang, Yu; Fan, Haochen; Huang, Jinhua; Yang, Lian-ming; Guan, Bo; Song, Yanlin
Abstract : Methylammonium bismuth iodide (MA3 Bi2 I9 ) perovskite has been deposited on a mesoporous TiO2 film through interdiffusion of solution-processed BiI3 /CH3 NH3 I stacking layers, and the resulting device was prepared and characterized. Abstract : Methylammonium bismuth iodide (MA3 Bi2 I9 ) perovskite, has been deposited on a mesoporous TiO2 film with high homogeneousity and coverage through interdiffusion of solution-processed BiI3 /CH3 NH3 I stacking layers, resulting in higher power conversion efficiency in the perovskite solar cell as compared with that prepared using a conventional one-step solution method.